2008
DOI: 10.1016/j.pain.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pain and tactile stimuli during arterial puncture in preterm neonates

Abstract: The purpose of this study was to assess the behavioral and physiological reactivity of preterm neonates during different phases of a blood collection procedure involving arterial puncture. The sample consisted of 43 preterm and very low birth weight neonates with a postnatal age of 1 to 21 days who were hospitalized in the Neonatal Intensive Care Unit. The neonates were evaluated during the whole blood collection procedure. The assessment was divided into five consecutive phases: Baseline (BL); Antisepsis (A),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
1
13
0
6
Order By: Relevance
“…Infants' physiological functions are not yet sufficiently mature to survive independently in the external environment [9]. Paradoxically, NICUs represent a risk factor for infants' development because of multiple painful, distressful, and uncomfortable stimuli [10,11]. For example, preterm neonates who were hospitalized in a NICU were found to be exposed to at least 44 acute stressful events and 24 chronic stressful events that were related to examinations and medical treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…Infants' physiological functions are not yet sufficiently mature to survive independently in the external environment [9]. Paradoxically, NICUs represent a risk factor for infants' development because of multiple painful, distressful, and uncomfortable stimuli [10,11]. For example, preterm neonates who were hospitalized in a NICU were found to be exposed to at least 44 acute stressful events and 24 chronic stressful events that were related to examinations and medical treatments [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that in- fants anticipated the reaction to painful stimulation of the arterial puncture, with significant changes in facial activity, HR, wakefulness and sleep, at the moment of antisepsis prior to arterial puncture. (9) When evaluating the set of physiological variables related to the blood gas procedure, it was found that RR was significantly lower five minutes after this practice in the newborn on MV, when compared to the time immediately after, with no influence of this variable for the groups in an Oxyhood and nasal CPAP. It is possible that, for this painful procedure, neonates using MV were more sensitive to pain, considering that all infants who were receiving this mode of oxygen therapy were premature and were not sedated.…”
Section: Discussionmentioning
confidence: 96%
“…During hospitalization in the NICU, preterm newborns experience an average of six painful procedures daily (Gaspardo, Chimello, Cugler, Martinez, & Linhares, 2008), and additionally suffer other extreme or moderate stressful events, such as, intubation, eye examination, lumbar puncture, heel pricks, and nasogastric tube insertion (Gorzílio, Garrido, Gaspardo, Martinez, & Linhares, 2015). The scientific, evidence-based, non-pharmacological management of neonatal acute pain (Cignacco et al, 2007;Fernandes, Campbel-Yeo, & Johnston, 2011) includes the following: (i) breastfeeding or human milk (as well as the unquestionable nutritional benefits of human milk for the infants, it is a potent pain relief intervention when used with breastfeeding or via oral-gastric tube); (ii) non-nutritive sucking (32 sucking behaviors per minute have an analgesic effect; a pacifier can be used); (iii) facilitatedtucking (placing the arms and legs of the infant near the trunk to maintain a flexed in utero posture, with limbs placed in body midline); (iv) swaddling (wrapping the infants in a sheet or blanket, limbs flexed, head, shoulders and hips neutral without rotation and hands accessible for exploration); (v) skin-to-skin (positioning of clinically stable infants against the breast of the mother allows them to be warmed, facilitates breastfeeding, sensitizes them to attachment, and relieves pain during medical procedures).…”
Section: Non-pharmacological Management Of Neonatal Painmentioning
confidence: 99%